The construction of the right social security in Brazil: Democracy, cirizenship and human rights (Revista Direitos Humanos e Democracia, 2026)
This study departs from the central problem of understanding the extent to which the normative Evolution of Social Security in Brazil has contributed either to the consolidation of fundamental rights or, conversely, to the perpetuation of historical mechanisms of inequality. This article examines the historical evolution of Social Security in Brazil, as well as significant infra-constitutional milestones. Employing a legal-historical approach, the study identifies normative advancements and political tensions that have shaped the Brazilian social security system. The research confirms the hypothesis that, despite the consolidation of Social Security as a fundamental right in the 1988 Constitution, structural inequalities persist due to its historical formation. It concludes that a critical understanding of this trajectory is essential for enhancing public policies aimed at social protection in democratic contexts.
Keywords: Social Security; Constitution; Fundamental Right; Human Dignity; Social Protection